Personalized information provision and the take-up of emergency government benefits: Experimental evidence from India - Amrit Amirapu; Irma Clots-Figueras; Bansi Malde; Anirban Mitra; Debayan Pakrashi; Zaki Wahhaj (University of Kent, School of Economics, 2022)
The COVID-19 pandemic has adversely affected the livelihoods of hundreds of millions of households, resulting in widespread poverty and food insecurity. To mitigate these effects, many governments have introduced additional benefits as part of their existing welfare schemes. However, there is often a gap between the introduction of these programs and access to the benefits. To shed light on the source of these gaps, we conduct a field experiment with just over 1,000 slum-dwelling households in Uttar Pradesh, India during the COVID-19 pandemic. The intervention randomly exposed individuals to personalised information about government benefits via cell phones. We find that the simple and low-cost provision of personalised information i) increased the accuracy and precision of participants' knowledge about their entitled benefits, ii) increased access to and utilization of benefits, and iii) improved wellbeing (as measured through consumption, food insecurity and mental health). We do not find significant differences in effects based on whether males or females are targeted. Our findings show that there are large gaps in knowledge of and access to government benefits (despite widespread publicity about the programs) which can be reduced via a simple and low-cost information intervention.
Keywords: D10; H53; I38; O12; 330; COVID-19; Government Benefits; Emergency Aid; Information Intervention